Improving Time of Arrival Estimation Using Encoded Acoustic Signals - João Miguel Fernandes Magalhães (2018)
Underwater localization systems are crucial to explore the sea. The most common systems for this environment use acoustic signals for position estimation and communication.There are several challenges that these systems have to tackle when using underwater acoustic signals. This dissertation will solely focus on the part of these systems that estimates the exact moment an acoustic signal has arrived, this is crucial, to establish an exact relative position.It is proposed the use of pseudorandom binary sequences modulated in BPSK. Such sequences have extremely low cross-correlation and high autocorrelation. Using this property, we hope that the correlation peak will render the exact moment a signal arrives.Also, given that it is possible to generate a set of orthogonal pseudorandom binary sequences, 16 of these sequences were generated and a symbol of 4 bits was assigned to each one of them. This way, the sequence being received can be identified and some data transmitted.